COAT PROTEIN MEDIATED RESISTANCE AGAINST TOBACCO STREAK VIRUS IN NICOTIANA TABACUM L. THROUGH RNA SILENCING - S. RAJAMANICKAM; G. CHANDRASEKAR; G. KARTHIKEYAN (The Bioscan, 2015)
The transgenic tobacco (Nicotiana tabacum L.) cv Abirami plants expressing hairpin RNA transcript (hpRNA) targeting coat protein gene of Tobacco streak virus (TSV) were generated and analyzed at the molecular and phenotypic levels. The coat protein (CP) genes of five isolates of TSV were sequenced (designated as CPCBE1, CPCBE2, CPDHP, CPKAR and CPCBE3) with view to develop transgenic tobacco resistance to Tobacco streak virus (TSV). The sequence analysis showed that they had a sequence identity of around 99 per cent at nucleotide level. The hairpin (hpRNA) construct was generated using the conserved sequences of coat protein gene of above TSV isolates. The hpRNA constructs corresponding to nucleotide positions 560 and 898 in the coat protein gene of TSV were introduced into tobacco (Nicotiana tabacum L.) cv. Abirami through Agrobacterium mediated transformation. The transgenic plants were screened and confirmed through PCR and Southern blot analysis using the genomic DNA. The transgenic T 0 tobacco plants showed resistance against TSV upon artificial mechanical inoculation of TSV without producing any symptoms of TSV, which was also confirmed by DAC-ELISA.